Empirical Analysis of the Impact of Exchange Rates on Economic Growth in Emerging Countries: Case of Morocco - Touzani, Ahmed; Brahim, Abidar (International Journal of Economics and Financial Issues, 2025)
This article analyzes the impact of exchange rate fluctuations on economic growth in emerging markets, with a particular focus on Morocco during the period 1994-2022. It employs an econometric methodology based on panel data to examine this complex relationship. The study highlights how exchange rate fluctuations, often rooted in economic fundamentals, can affect economic growth through various channels, including investment, foreign trade, and financial development. The results reveal a negative correlation between exchange rate depreciation and economic growth, suggesting that prudent exchange rate management is crucial to supporting economic development. The conclusions emphasize the importance of a well-calibrated exchange rate policy to maintain sustainable competitiveness and promote economic growth in developing countries.